Exploring the relationship between climate change events and migration decisions: Evidence from a choice experiment in Bangladesh - Ong Quoc Cuong; Suza, Ma; Savelli, Adam; Nelson, Katherine M. (Elsevier, 2024)
Bangladesh is a low-lying deltaic nation with high vulnerability to climate-related hazards. Hatiya Island is located in Southern Bangladesh, and residents rely significantly on fishing and agriculture for their livelihoods. However, the island's primary production systems face a threat from intense and frequent sudden onset environmental hazards such as river erosion, cyclones, and flooding, as well as slow onset environmental hazards like saline intrusion, tidal inundation, and rising temperatures. Little is known about the effect sudden onset and slow onset hazards have on the migration patterns of Hatiya's residents. The aim of this study is to investigate the relationship between climatic events and the migration decisions of residents on Hatiya Island. To explore this link, we collected empirical data from 337 respondents on Hatiya Island using a choice experiment survey. The five attributes were used to construct migration scenarios, including climate events at Hatiya Island, the distance of migration, the migration type, the social network at the potential destination, and the difference in income between Hatiya Island and the potential destination. The findings from the mixed logit model indicated that climate events at Hatiya, migration distance, and income gap affected residents' migration decisions. Extreme slow onset change and extreme sudden onset change were less likely to induce migration compared to the moderate level of slow and sudden onset change. However, residents were more likely to migrate as the income difference between Hatiya and the prospective destination increased. Residents were willing to migrate at a 9.4 % increase in income for extreme sudden onset change, while residents required a 14.19 % increase in income to migrate in response to extreme slow onset change. As such, policies are needed to support migrants in receiving areas through improved social protection systems, to support migrant-sending households' transformative adaptation in origin areas, and to bolster community-driven adaptation initiatives in Hatiya. The findings from this study can contribute to the existing literature on the relationship between environmental hazards and mobility and inform policymakers on how to design policies that support vulnerable populations.